The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1210/jc.2013-4305
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Increasing Glucocorticoid Replacement Dose on Cardiovascular Risk and Insulin Sensitivity in Patients With Adrenocorticotrophin Deficiency

Abstract: Endothelial dysfunction may contribute to the increased cardiovascular mortality associated with higher glucocorticoid doses. This may be a direct glucocorticoid effect, not mediated by insulin resistance. ACTH-deficient patients should thus be prescribed the lowest safe glucocorticoid replacement dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 38 publications
3
42
1
Order By: Relevance
“…The consequences of temporary hypercortisolism following therapy with HC are unknown so far [5] but have been described to be associated with deleterious effects on body composition. In fact, higher glucocorticoid replacement doses may have adverse effects on both body fat and lipid profile [3] as well as on endothelial function [7]. However, our findings did not support this effect, which has been thought to be associated with increased overall mortality, at least in patients with non-functioning pituitary adenoma and hormonal insufficiency [9].…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…The consequences of temporary hypercortisolism following therapy with HC are unknown so far [5] but have been described to be associated with deleterious effects on body composition. In fact, higher glucocorticoid replacement doses may have adverse effects on both body fat and lipid profile [3] as well as on endothelial function [7]. However, our findings did not support this effect, which has been thought to be associated with increased overall mortality, at least in patients with non-functioning pituitary adenoma and hormonal insufficiency [9].…”
contrasting
confidence: 70%
“…Adenomas are the most common disease affecting the pituitary with an estimated prevalence of 16.7% [4]. Compared to a normal population, patients with hypopituitarism are at greater risk to develop cardiovascular and cerebrovascular disease, conditions associated with higher mortality [1,7]. Increased cardiovascular mortality in hypopituitarism may be the direct effect of inadequate availability and action of pituitary hormones.…”
mentioning
confidence: 99%
“…ACTH deficiency leads to hypocortisolism during acute illness,27 with a significant risk of life‐threatening adrenal crisis. It is also intimately associated with the adverse metabolic effects of chronic supraphysiological glucocorticoid replacement 18, 28. We have shown that mortality risk is increased almost fourfold in patients taking total daily hydrocortisone doses of 30 mg or higher.…”
Section: Discussionmentioning
confidence: 99%
“…We have undertaken a series of linked clinical studies to assess if plasma TSP1 and/or TSP1 mRNA expression in PBMC in healthy volunteers are acutely upregulated by dexamethasone; if plasma TSP1 is elevated in patients with Cushing's syndrome; and if plasma TSP1 in patients with secondary adrenal insufficiency is adequately sensitive to detect a small change in the hydrocortisone dose. Patients with secondary adrenal insufficiency " Plasma was available from 16 of 17 patients with secondary adrenal insufficiency (eight male and eight female, median age 56 years, range 22-87), who participated in a study investigating the effects of an increase in the hydrocortisone dose on cardiovascular risk markers and insulin sensitivity (24). Samples were collected fasting w2 h after the morning hydrocortisone dose when on a standard dose of %20 mg/day (median 16 mg/day, range 10-20 mg) and 1 week after hydrocortisone was increased to 30 mg/day.…”
Section: Introductionmentioning
confidence: 99%